2021
DOI: 10.1088/1478-3975/abef79
|View full text |Cite
|
Sign up to set email alerts
|

Operating principles of circular toggle polygons

Abstract: Decoding the dynamics of cellular decision-making and cell differentiation is a central question in cell and developmental biology. A common network motif involved in many cell-fate decisions is a mutually inhibitory feedback loop between two self-activating 'master regulators' A and B, also called as toggle switch. Typically, it can allow for three stable states -(high A, low B), (low A, high B) and (medium A, medium B). A toggle triad -three mutually repressing regulators A, B and C, i.e. three toggle switch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…One such architecture recently explored was a serial and parallel connection of positive feedback loops, where the authors showed that a parallel architecture might help in limiting cell-cell variability, and hence is a preferred architecture in differentiation networks (10) . In previous work, we had explored a variety of the serial connection, a cyclic chain of MI motifs labelled circular toggle polygons (29) . Given the additional feedback embedded in the circular/cyclic connection, it should be a better candidate for a synchronous expression of nodes potentially leading to the stabilization of cell-fates.…”
Section: Discussionmentioning
confidence: 99%
“…One such architecture recently explored was a serial and parallel connection of positive feedback loops, where the authors showed that a parallel architecture might help in limiting cell-cell variability, and hence is a preferred architecture in differentiation networks (10) . In previous work, we had explored a variety of the serial connection, a cyclic chain of MI motifs labelled circular toggle polygons (29) . Given the additional feedback embedded in the circular/cyclic connection, it should be a better candidate for a synchronous expression of nodes potentially leading to the stabilization of cell-fates.…”
Section: Discussionmentioning
confidence: 99%